ChemInform Abstract: A Mild, Palladium‐Catalyzed Method for the Dehydrohalogenation of Alkyl Bromides: Synthetic and Mechanistic Studies. Issue 9 (5th March 2013) - Bissember, Alex C.; Levina, Anna; Fu, Gregory C.
Abstract The elimination from functionalized aliphatic organic halides is studied in the presence of base and a Pd‐phosphine catalyst.